Kritik terhadap Fikih Poligami: Studi atas Pemikiran Siti Musdah Mulia - Zulfitri Zulkarnain Suleman; Zulkarnain Suleman (Al-Mizan (e-Journal), 2019)
This paper discusses about the Siti Musdah Mulia’s thought about polygamy in Islam. This research is a library research with primary data sources are the writings of Siti Musdah Mulia about women, especially polygamy. Data were analyzed descriptively qualitatively with a sociological approach to law. The results showed that Siti Musdah Mulia refuted polygamy because it was considered to insult and insult women's dignity. The Marriage Law and Compilation of Islamic Law which legalize polygamy favor the interests of men and ignore women. The provisions of polygamy in the Marriage Law and KHI have psychological implications for women; violence against women; and social towards the community. Whereas the principle of ushul fiqh is to reject the negative excesses rather than benefit.